Systematic Literature Review: Tourism Development Factors in the Global Era - Anwar, Muhammad Khairul; Aprilianisa, Nathya Kyra (Indonesia Berdaya, 2024)
This research attempts to produce a determinant model of Tourism Development that is novel and observable for future empirical research on tourism development in Indonesia. Furthermore, this study aims to inform stakeholders to identify strategies to combat tourism sustainability challenges in the global era. This study uses a literature review study with variable mining, a systematic literature review (RSL) using RStudio, bibliometric and VOSViewer software. The data used is the minimum limit of English-language journal articles available in the Scopus electronic database from the last 5 years, i.e. 2019 - 2023, and selected based on the title created by the author. Nowadays, the publication of articles in journals is growing rapidly and can be found on the Internet. Exploring variables to explore and identify variables that drive tourism development through Traditional Literature Review (TLR) or Narrative Literature Review (NLR) is inefficient and ineffective. A possible solution is to use the concept of big data, namely Systematic Literature Review (SLR). The author found 3791 articles on Tourism Development in Scopus. Research on the topic of tourism development can be carried out in different countries and the developments on this topic are very good. The author took 6 tourism development models with specific characteristics: people, economy and social impacts, tourism industry, ecotourism, tourist destination and tourism management.